Constructing an organized and coherent text: how discourse markers are viewed by Iranian post-graduate students? - Kalajahi, Seyed Ali Rezvani; Abdullah, Ain Nadzimah; Baki, Roselan (Center for Promoting Ideas, 2012)
The purpose of this study is to explore how five Iranian post-graduate students view discourse markers (DMs) and if there is any distinction between what is expressed in the interview and their writing samples. A qualitative method is being employed in the study. Purposive sampling is conducted in selecting the students. The findings indicate that all informants are fully aware of applying DMs in their writing but they do not have sufficient knowledge for the proper use and choosing appropriate ones. The findings are very specific and never mentioned in the previous research studies. However, more research needs to be undertaken in order to address the diversity of students with a bigger sample and various methodology.